Effect of different bracket types on streptococcus mutans count in orthodontic patients using fluoridated toothpaste - Jasim , Hala M; Al-Dabagh, Dhiaa A; Mahmood, Maha A. A (Journal of Baghdad College of Dentistry, 2020)
Background: Plaque retention during fixed orthodontic therapy is an important cause of developing enamel demineralization. The purpose of this study was to evaluate the effect of different brackets types on the count of Streptococcus Mutans in orthodontic patients using conventional fluoridated toothpaste. Materials and Methods: Plaque samples were collected from maxillary 1st premolar teeth of twenty right handed patients (using split mouth technique) before bonding, after 48 hrs of bonding using tooth brush only, and after 2 weeks of using fluoridated toothpaste. Stainless steel bracket was bonded on right first premolar while the left one was bonded with sapphire bracket. The calculation of the Streptococcus Mutans count was done using the plate counting method utilizing colony counter. The differences between the two types of brackets were determined using the Wilcoxon signed ranks test. Results: The median bacterial count on the right side was insignificantly higher than the left side; streptococcus mutans in the plaque sample around the sapphire brackets showed insignificantly less counts than around the stainless steel one, when the patients used tooth brush only or fluoridated toothpastes. Fluoridated toothpastes reduced streptococcus mutans insignificantly around both types of brackets. Conclusion: Fluoridated toothpaste acts effectively in reducing streptococcus mutans colony counts around sapphire and stainless steel brackets. Keywords: Streptococcus mutans, Stainless steel brackets, Sapphire brackets.